Legal politics of the governor’s position in ratio legis on the regulatory aspects of regional government - Ampera Ariyanto; Tomy Michael (Technium Social Sciences Journal, 2024)
In formation of laws and regulations, Article 18 paragraph (1) of the 1945 Constitution shows that relationship between the central government and provincial government is a multilevel relationship. The governor runs the government in provincial area based on principle of deconcentration, namely the delegation of authority from central state equipment to subordinate agencies to carry out certain work in administration of government. Article 18 paragraph (2) of 1945 Constitution Republic Indonesia shows that relationship between the provincial government and regency/city government is an equal relationship because the Governor and Regent/Mayor both run government in their respective regions based on principles of decentralization (regional autonomy) and assistance tasks. The Governor has a dual position or role, namely as the head of provincial region (Local Self Government) as well as the Regional Head/Representative of Central Government in the region (Local State Government. The governor has a dual role as head of the province and head of the region (representative of the central government). Law 23/2014 on Local Government tends to emphasize the role of governor as a representative the government through of administration government based on principle of deconcentration. The task of maintaining integrity of government system is a goal. The strengthening of governor’s role as the government’s representative through several forms of governor interference in implementation government in district/city aims to maintain the balance and harmony of government relations. The central government must prevent country from disintegration by controlling all forms of local government activities. The central government is fully responsible for implementation of government both at center and in the provinces and districts / cities.